Pengaruh Kualitas Pelayanan dan Variasi Produk terhadap Kepuasan Konsumen pada Usaha Kue di Medan (Studi Kasus pada Ulfakue Medan) - Zafira Anggreni; Amrin Mulia Utama Nasution (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to determine the effect of service quality and product variety on customer satisfaction at Ulfakue Medan. The research method used is a quantitative method with an associative approach. The sampling technique applied was non-probability sampling using purposive sampling. The population in this study consisted of all customers who had purchased products from Ulfakue Medan, with a total sample of 97 respondents. Data were analyzed using descriptive statistical analysis and multiple linear regression analysis with the assistance of SPSS software. The research findings are as follows: (1) Based on the partial test (t-test), the service quality variable (X1) obtained a t-value of 5.226, which is greater than the t-table value of 1.661, with a significance value of < 0.05. Thus, H1 is accepted, indicating that service quality has a positive and significant effect on customer satisfaction at Ulfakue Medan. The product variety variable (X2) obtained a t-value of 3.764, which is greater than the t-table value of 1.661, with a significance value of < 0.05. Therefore, H2 is accepted, indicating that product variety has a positive and significant effect on customer satisfaction. (2) Based on the simultaneous test (F-test), the F-value obtained was 86.147, which is greater than the F-table value of 3.09, with a significance value of < 0.05. This indicates that service quality and product variety simultaneously have a positive and significant effect on customer satisfaction at Ulfakue Medan. (3) Based on the coefficient of determination (R²) test, the Adjusted R Square value was 0.639, indicating that 63.9% of the variation in customer satisfaction can be explained by service quality and product variety, while the remaining 36.1% is explained by other factors not examined in this study.